2010
DOI: 10.1111/j.1365-2796.2010.02228.x
|View full text |Cite
|
Sign up to set email alerts
|

Pain inhibition and postexertional malaise in myalgic encephalomyelitis/chronic fatigue syndrome: An experimental study

Abstract: Abstract. Van Oosterwijck J, Nijs J, Meeus M, Lefever I, Huybrechts L, Lambrecht L, Paul L (Vrije Universiteit Brussel, Brussels; Artesis University College Antwerp, Antwerp; University Hospital Brussels, Brussels; Private Practice For Internal Medicine, Ghent ⁄ Aalst; CVS Contactgroep, Bruges; Belgium; and University of Glasgow, Glasgow, UK). Pain inhibition and postexertional malaise in myalgic encephalomyelitis ⁄ chronic fatigue syndrome. J Intern Med 2010; 268: 265-278.Objectives. To examine the efficacy o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
104
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(111 citation statements)
references
References 46 publications
7
104
0
Order By: Relevance
“…138 A controlled study comparing patients with CFS to sedentary healthy control volunteers during two types of controlled exercise (submaximal, and self-paced physiologically limited) found that pain thresholds following exercise increased in controls, but decreased in patients with CFS. 139 These studies suggest, but do not prove, a physiologic basis for the postexertional malaise reported by a high fraction of patients with CFS.…”
Section: Evidence Of Mitochondrial Dysfunction Oxidative and Nitrosamentioning
confidence: 95%
“…138 A controlled study comparing patients with CFS to sedentary healthy control volunteers during two types of controlled exercise (submaximal, and self-paced physiologically limited) found that pain thresholds following exercise increased in controls, but decreased in patients with CFS. 139 These studies suggest, but do not prove, a physiologic basis for the postexertional malaise reported by a high fraction of patients with CFS.…”
Section: Evidence Of Mitochondrial Dysfunction Oxidative and Nitrosamentioning
confidence: 95%
“…9,26,58,64 However, questions were raised regarding the effect of exercise on patients with faulty modulation systems. 33,65,66 The goal of this study was to investigate the predictive value of the EIH profile on pain intensity in a rat model of nerve injury. Extrapolating from studies on CPM, we hypothesized that rats with less efficient EIH would develop more severe pain following nerve injury.…”
mentioning
confidence: 99%
“…[14] Moreover, neurological testing has been suggested for structural and functional abnormalities [15] as well as sleep studies. [16] Also, monitoring for PENE, [17,18] and tilt table tests for the presence of orthostatic intolerance [19] have been listed. The International Consensus Primer is the first to include profiling of the immune system, particularly for reduction in Natural Killer cell function, [20] a possible increase in cytoxicity, [21] and for signs of intestinal dysbiosis.…”
Section: Laboratory and Further Investigationsmentioning
confidence: 99%